The Effect of Counseling Based on Functional Analytic Psychotherapy with Enhanced Cognitive Therapy on Married Adolescent Women’s Sexual Self-efficacy: A Prospective Study - Maryam Gholami; Katayoun Alidousti; Mozhgan Taebi; Yunes Jahani; Atefeh Ahmadi (Clinical and Experimental Obstetrics & Gynecology)
Background: Sexual well-being is a vital aspect of the overall quality of life. Sexual self-efficacy is a key factor in improving of women’s sexual well-being. This study aimed to determine the effect of counseling based on functional analytic psychotherapy (FAP)-enhanced cognitive therapy (CT) on sexual self-efficacy in married adolescent women. Methods: This prospective clinical trial, conducted in 2019, used a pre-test/post-test design with a control group. The study included 80 urban and rural married adolescents who met the inclusion criteria and were referred to the health centers in Darab and surrounding villages. Out of 350 participants, 150 adolescents were included in the study and were allocated to two groups. The counseling program for the intervention group was carried out by the researcher over 16 sessions, held twice a week for 90 minutes each. In contrast, the control group received routine education. The intervention group received counselling based on FAP-enhanced CT, while the control group did not receive this training during the study. The data collected from the questionnaires were imported into SPSS 24, and analyses were performed using analysis of covariance (ANCOVA), paired t-test, and independent t-test. Results: There was no significant difference in sexual self-efficacy between the two groups at pre-test time (p > 0.05); however, a significant difference was observed at post-test (p < 0.0001). Additionally, there was a significant difference between the mean scores of sexual self-efficacy before and after the intervention in the intervention group (p < 0.0001), while no significant difference was observed in the control group (p = 0.25). Conclusion: The results suggest that counselling based on FAP-enhanced CT provided to married adolescent women significantly improves their sexual self-efficacy. Clinical Trial Registration: The trial protocol was registered with the Iranian Registry of Clinical Trials on 16/06/2019, IRCT20190217042736N1 (https://www.irct.ir/trial/37718).